2016
DOI: 10.1155/2016/3627463
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Evaluation of the Antimicrobial Effect of Propolis with Chlorhexidine against Oral Pathogens: An In Vitro Study

Abstract: This study aimed to compare the antimicrobial effectiveness of ethanolic extract of propolis (EEP) to chlorhexidine gluconate (CHX) on planktonic Streptococcus mutans, Streptococcus sobrinus, Lactobacillus acidophilus, Lactobacillus salivarius subsp. salivarius, Aggregatibacter actinomycetemcomitans, Prevotella intermedia, Porphyromonas gingivalis, Staphylococcus aureus, Enterococcus faecalis, Actinomyces israelii, Candida albicans, and their single-species biofilms by agar dilution and broth microdilution tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 43 publications
8
77
0
16
Order By: Relevance
“…However, Grampositive bacteria were more sensitive than Gram-negative bacteria. The same results were demonstrated by Akca et al (2016). Popova et al (2005) found that the antibacterial activity of whole propolis samples from six different regions of Turkey was active against bacterial strains (Gram positive and Gram negative), while Grange & Davey (1990) observed a high antimicrobial activity of propolis against Gram-positive bacteria and limited activity against Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 67%
“…However, Grampositive bacteria were more sensitive than Gram-negative bacteria. The same results were demonstrated by Akca et al (2016). Popova et al (2005) found that the antibacterial activity of whole propolis samples from six different regions of Turkey was active against bacterial strains (Gram positive and Gram negative), while Grange & Davey (1990) observed a high antimicrobial activity of propolis against Gram-positive bacteria and limited activity against Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 67%
“…[136][137][138] In a recent study by Akca et al, 138 the effects of both CHX and propolis were found to be equal against biofilms of Streptococci, and the authors also found propolis to be more effective in inhibiting Gram-positive than Gram-negative bacteria. The potency of propolis against Gram-positive bacteria has also been reported by Nieva Moreno et al 139 and Kujumgiev et al 140 …”
Section: Antimicrobial Effectivenessmentioning
confidence: 98%
“…These differences are depending on botanical, geographical and seasonal conditions 48 leading to differences in antimicrobial potency more than 100-fold in-between different honeys. 49 Also, propolis MIC has more widely range from 1.0 up to 100 27,45,[50][51][52][53] and may be of very weak potency reaching≥500 54 mg/L depending on very wide range of different propolis constituents from different geographic regions. 24,27,52 Honey possesses antibacterial activities depending on physicochemical properties such as osmotic pressure, low pH of 3 to 4.5 and non-peroxide factors (phytochemicals) as polyphenols, 55 as well as peroxide effects due to H 2 O 2 level in honey which is a strong predictor of its antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%